Self-doped graphite nanobelts. (April 2023) - Camargo, Bruno Cury; El-Kerdi, Banan; Alaferdov, Andrei; Zuri, Shahar; Birowska, Magdalena; Escoffier, Walter
Abstract: We report that mechanical deformation of graphite with cavity shock waves introduces a new group of charge carriers, with both effective mass and native concentration one order of magnitude above those found in the pristine material. Their nature, however, remains quasi-2D. Our results show that defects introduced during mechanical exfoliation have the potential to unlock oscillatory behavior above 50 T in graphite, thus providing a new probe for field-induced electronic phase transitions in the material. Graphical abstract: